Are Schools Library Services equipped to survive in the Age of Information? - David Streatfield; Sharon Markless (Information Research: An International Electronic Journal, 2000)
Describes the results of an investigation in the the factors that would affect the survival and growth of School Library Services in England and Wales, including funding, staffing and service priorities. The main area of weakness identified is that most Services are not well placed to demonstrate the effectiveness of their provision in relation to the current government's and schools' agendas.